ANALISIS STRATEGI PENGNEMBANGAN UKM AGRIBISNIS BERBASIS KEDELAI DI KOTA BATURAJA KABUPATEN OGAN KOMERING ULU (JASEP, 2017)
This research is for analysis of development strategy on soybean based SME in Baturaja City, This research was conducted in February until april 2017 in Baturaja City OKU Regency The method used in this research is survey method, sampling in this research using saturated sampeling method, the samples taken are the perpetrators of soybean based SMEs such as tempe, tofu, and soy milk in Kota Baturaja The type of data used in this study includes primary data, and secondary, which is analyzed by using SWOT matrix. The results of the field study obtained an average of 3.21 internal factors And external factor 3,65 this means soybean based small and medium enterprises in Baturaja City OKU Regency is in position 1 With a concentration strategy through vertical integration, from analysis SWOT Can be drawn that conclusion small and medium enterprises Soybean-based agribusiness in Baturaja City has weaknesses and threats that must be minimized In order to develop more advanced in the future is in several ways. Small and medium enterprises Soy based should, improve marketing, Produce quality products, Increase production volume, Modern and appropriate technology update, guidance on UKM, innovation and product modification.